KEARIFAN LOKAL (LOCAL WISDOM) DALAM PRAKTIK BISNIS DI INDONESIA - Wijayanto, Andi (FORUM, 2012)
The phenomenon of globalization is increasing the importance of various studies on localwisdom. The lack of study of the local wisdom values in business practices in Indonesia encouragesauthors to identify those values. Method of data collection using literature study. The identificationresults find there are various indigenous values. that form the basis for a variety of business practices inIndonesia. These values. generally varied according to ethnicity given that Indonesia consist of variousethnics. Generally, in every ethnic or a communal in Indonesia, values. can be found, either on theJavanese, Sundanese, Bali, Lombok, Minang, Dayaks, Bugis, to Papua. Research on local wisdomespecially from an economic and business standpoint is important to be done. But more important ishow to socialize these values. to the younger generation so it does not disappear replaced by globalvalues.